Report of the Committee on Finance for the Private Sector - Planning Commission (Planning Commission, 1954)
In a press communique dated the 5th October 1953, the Reserve Bank of India announced the setting up of a Committee under the Chairmanship of Shri A. D. Shroff to examine how increased finance could be made available to the private sector. The communique reads as follows : The Planning Commission have assigned an important role to the private sector in the implementation of the National Plan. Investment in this sector has not, however, reached the level envisaged in the Commission’s Report. The Taxation Enquiry Commission is investigating the effects of the structure and level of taxation of income on capital formation and on maintenance and development of productive enterprise.
Reserve Bank of India Bombay
Reserve Bank of India Bombay